Space as Story. Cartographic Strategies in Christoph Ransmayr’s Atlas eines ängstlichen Mannes - Maldonado-Alemán, Manuel (Revista de Filología Alemana, 2021)
This article, which is inserted in the framework of Spatial Literary Studies, aims to inquire about the cartographic functioning of Christoph Ransmayr’s Atlas eines ängstlichen Mannes, which constitutes an illustrative example of the so-called literary cartography. Starting from a mobile and off-centered perspective, typical of a horizontal vision of space, the work establishes an alternative model to the spatiality imposed by hegemonic cartographic practices, while at the same time projecting a critical view on tragic moments of recent human history, on scenarios of destruction and desolation.